Generation expansion planning with wind power plant using DE algorithm. (2023) - Ramkumar, A.; Rajesh, K.
Abstract: To sustain the economic growth, infrastructure development is only of the essential aspects and also the power sector is the most important infrastructure elements. For the increment of energy demand, apart from the conventional energy sources, the wind, solar etc., of the necessary sources to produce the electrical energy to meet out the demand. The conventional sources of energy associated with many problems like, prices increased for petroleum products, environmental implications, safety from radiations, global warming etc. To overcome the difficulties in association with conventional energy sources, most of the countries including India have shifted the attention for improving renewable energy sources. In practical, the Generation Expansion Planning (GEP) problem is a large scale and complex. Also the nonlinear optimization problem of mixed integer nature where the number of candidate solutions to be evaluated increases exponentially with system size. By the effective planning of power systems can be achieved by the accurate solution of the GEP problem. The aim of this paper is to apply the Differential Evolution (DE) algorithm to the GEP problem and find out the least cost expansion plan. It is applied for a test system of six and fourteen years planning horizons. As the wind energy composition in the system is continuously growing, the impact of the same has been studied. The different cost component with variations and also the reliability indices are studied.